Child-Friendly School Policy with Children’s Rights Approach in Bekasi City - Suharjuddin Suharjuddin; Markum Markum (Universitas Cokroaminoto Palopo, 2021)
Child-friendly and students based school is one of new paradigm in providing high quality and innovative education in Indonesia. The objective of this research is to explain the outcome of the implementation of Child Friendly School Policies established by the Ministry of Female Empowerment and Child Protection in Bekasi city. The sub focus in this research are (1) implementation of Child-friendly teaching and learning, (2) Child-friendly facility & infrastructure, (3) Participation of parents, community institutions, stakeholders, business and alumnus. This study used a qualitative method in case study approach in SDN Teluk Pucung 1. The factors that support the implementation of the Child Friendly School Policy at SDN Teluk Pucung 1 are good and smooth communication, attitudes and commitment of all school people, coordination between the Bekasi Government and the School and the positive support of all school members, parents, and surrounding communities. The conclusion: (1) implementation of child friendly teaching-learning process has fulfilled the criterion of child-friendly school. (2) Implementation of facilities has followed the regulation and showed child-friendly condition, (3) participation of parents, community organizations, stakeholders, business and alumnus is still low and need to be improved in the future time. Suggestion and recommendations are provided for improvement and development towards the implementation of child-friendly school in Bekasi City. Key Words: Child-friendly school, students based, Policy implementation.